Competence as a Mediator of Technical Training and Human Resource Development on the Commitment of Palembang MSME Entrepreneurs - Devi Aprilia Karisma; Afriyadi Cahyadi; Zunaidah Zunaidah (International Journal of Management Science and Information Technology, 2026)
MSMEs are essential for boosting the economy, creating jobs, and enhancing community welfare. Enhancing the commitment of MSME operators is still hampered by issues with human resources (HR) quality, training access, and business legality. This study uses competence as a mediating variable to examine how technical training and HR development affect MSME operators' commitment. The study uses a cross-sectional survey method with an explanatory quantitative approach. 200 SME operators from Palembang City's Ilir Timur II Subdistrict make up the sample, which was chosen by chance. A questionnaire was used to gather the data, and Structural Equation Modeling–Partial Least Squares (SEM-PLS) was used for analysis. The results indicate that technical training and HRD have a positive and significant effect on the commitment of MSME entrepreneurs, with competence acting as a significant mediator. Technical training and human resource development were found to enhance competence, while competence significantly influences commitment. Additionally, competence has a major role in mediating the impact of technical training and human resource development on commitment, making it the main mechanism for enhancing sustainability and corporate loyalty. These findings support the Human Capital Theory, which states that investments in training and human resource development may improve capabilities as human capital and build commitment. Therefore, SME development programs should focus on fostering practical and sustainable competencies to enhance competitiveness and business sustainability. This study suggests that policymakers should prioritize competency-based training and mentoring to strengthen MSME commitment, competitiveness, and sustainability.